Age-related behavioural abnormalities in C57BL/6.KOR–Apoe shl mice - Ueno Hiroshi; Takahashi Yu; Mori Sachiko; Kitano Eriko; Murakami Shinji; Wani Kenta; Miyazaki Tetsuji; Matsumoto Yosuke; Okamoto Motoi; Ishihara Takeshi (Translational Neuroscience)
Spontaneously hyperlipidaemic (Apoeshl) mice were discovered in 1999 as mice lacking apolipoprotein E (ApoE) owing to a mutation in the Apoe gene. However, age-related behavioural changes in commercially available Apoeshl mice have not yet been clarified. The behavioural abnormalities of ApoE-deficient mice, which are genetically modified mice artificially deficient in ApoE, have been investigated in detail, and it has been reported that they can serve as a model of Alzheimer’s disease (AD). To understand whether Apoeshl mice can also serve as a murine model of AD, it is necessary to investigate age-related behavioural abnormalities in Apoeshl mice. In this study, we conducted a series of behavioural experiments on 7- and 11-month-old Apoeshl mice to investigate the behavioural abnormalities associated with ageing in Apoeshl mice. In this study, 7-month-old Apoeshl mice showed decreased body weight and grip strength compared to age-matched wild-type mice. In the open field test, 7-month-old Apoeshl mice showed increased anxiety-like behaviour compared to wild-type mice, whereas 11-month-old Apoeshl mice showed decreased anxiety-like behaviour. Moreover, Apoeshl mice aged 7 and 11 months had increased serum cholesterol levels. These results indicate that the behaviour of Apoeshl mice changes with age. However, 11-month-old Apoeshl mice did not show a decline in cognitive function or memory ability similar to murine models of AD. Our findings indicate that Apoeshl mice can be used to investigate the function of ApoE in the central nervous system.